Four new species of Brueelia Kéler, 1936 (Phthiraptera: Ischnocera: Philopteridae) from African songbirds (Passeriformes: Sturnidae and Laniidae) - Gustafsson, Daniel R.; Bush, Sarah E. (Zootaxa, 2015)
Four new species in the louse genus Brueelia Kéler, 1936 are described from African hosts of the families Sturnidae and Laniidae. They are: Brueelia rigbyi n. sp. ex Corvinella melanoleuca (Jardine, 1831), B. clara n. sp. ex Lamprotornis australis (A. Smith, 1836), B. tkachi n. sp. ex Spreo albicapillus albicapillus Blyth, 1856, and B. coryliventer n. sp. ex Creatophora cinerea (Meuschen, 1787). These four species are characterized by a unique abdominal chaetotaxy and a sinuous thickening of the distal margin of the male mesosome. These four species are very similar, and we consider them to form one species group. A key to the species of the group is provided.